Influence of Particle Reinforcement and Heat Treatment on the Wear Resistance of Inductively Melted Hardpaint Coatings - Patrick Schwarz; Sebastian Weber; Friederike Deuerler (Metals, 2020)
Wear-resistant coatings can reduce the high economic damage caused by wear processes. In this study, various protective layers based on the alloy X400CrVMo17-15-2 were investigated. Commonly, the prealloyed metal powder is used for plasma transferred arc powder surfacing. However, in this work, the cost-efficient hardpaint technology was used to produce particle-reinforced (fused tungsten carbides) and non-reinforced coatings. To analyze the wear behavior, the coatings were subjected to abrasion wear and scratch tests. For the abrasion wear test, a grinding pin (Al2O3) is pressed with a defined force against the surface of the rotating sample for 6 h. For the scratch test, a loaded diamond pyramid indenter was employed to create a circular groove on the coatings at a predefined speed. The wear grooves were analyzed with the aid of laser scanning microscopy. In comparison to the coatings in the as-processed condition, the non-reinforced protective layers were investigated after quenching, with and without deep cryogenic treatment, and tempering. The determination of proper heat treatment parameters was supported by computational thermodynamics. It has been confirmed that it is possible to improve the wear resistance of the unreinforced coatings by heat treatment. However, the reinforced layers showed the highest resistance against abrasion.